2016
DOI: 10.1063/1.4944788
|View full text |Cite
|
Sign up to set email alerts
|

Upgraded metallurgical-grade silicon solar cells with efficiency above 20%

Abstract: We present solar cells fabricated with n-type Czochralski-silicon wafers grown with strongly compensated 100% upgraded metallurgical-grade feedstock, with efficiencies above 20%. The cells have a passivated boron-diffused front surface, and a rear locally phosphorus-diffused structure fabricated using an etch-back process. The local heavy phosphorus diffusion on the rear helps to maintain a high bulk lifetime in the substrates via phosphorus gettering, whilst also reducing recombination under the rear-side met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…However, when a sister silicon wafer underwent a boron diffusion, as outlined in section 3.1, a significant reduction in the bulk lifetime was observed, where τ bulk values of <2 ms were measured. Although the boron-diffused wafer shows a lower τ bulk than the cell wafers shown inFigure 9A, we postulate that the τ bulk of the cell wafers has been preserved by the heavy phosphorus diffusion, in which case some gettering has occurred as previously demonstrated in Zheng et al33…”
supporting
confidence: 65%
See 1 more Smart Citation
“…However, when a sister silicon wafer underwent a boron diffusion, as outlined in section 3.1, a significant reduction in the bulk lifetime was observed, where τ bulk values of <2 ms were measured. Although the boron-diffused wafer shows a lower τ bulk than the cell wafers shown inFigure 9A, we postulate that the τ bulk of the cell wafers has been preserved by the heavy phosphorus diffusion, in which case some gettering has occurred as previously demonstrated in Zheng et al33…”
supporting
confidence: 65%
“…However, when a sister silicon wafer underwent a boron diffusion, as outlined in section 3.1, a significant reduction in the bulk lifetime was observed, where τ bulk values of <2 ms were measured. Although the boron‐diffused wafer shows a lower τ bulk than the cell wafers shown in Figure A, we postulate that the τ bulk of the cell wafers has been preserved by the heavy phosphorus diffusion, in which case some gettering has occurred as previously demonstrated in Zheng et al . Although we do not understand the cause for the large reduction in τ bulk following the boron diffusion, we can postulate that some level of contamination has occurred during this process, which could be reduced by removing the BRL by a wet chemical process to prevent any impurities in the BRL being diffused into the bulk material during the traditional in situ oxidation to dissolve the BRL .…”
Section: Resultsmentioning
confidence: 62%
“…However, UMG-Si contains more impurities, resulting in lower efficiency of crystalline silicon solar cells made from such materials than from the conventional Siemens process. Thanks to the improvements in the UMG purification process, Zheng et al, in 2016 [7] reported solar cells fabricated with 100% UMG-Si with peak efficiency of 20.9%, and 21.9% for a control device made from electronic grade silicon. Nevertheless, the potential advantage of low cost can be impaired if outdoor efficiency is reduced by degradation of quality due to high concentration of metallic and non-metallic impurities [8].…”
Section: Introductionmentioning
confidence: 99%
“…Using this effective defect density and knowing the capture cross section ratio of the BO defect in n-type silicon, 26) we can then simulate the excess carrier density at open circuit for a range of temperatures and light and intensities. To do this we used the cell parameters from 23) and the QSSCell tool. 27) Table II shows the determined excess carrier concentration during BO generation.…”
Section: Estimation Of the Injection Level During Bo Activationmentioning
confidence: 99%